Factors influencing nurses' behavioral intention toward caring for COVID-19 patients on mechanical ventilation: A cross-sectional study. - Jingxia Cheng; Jinbo Cui; Wenwen Yu; Hua Kang; Yongming Tian; Xiaolian Jiang (PLoS ONE, 2021)
Objectives To investigate nurses' behavioral intention toward caring for COVID-19 patients on mechanical ventilation, as well as the factors affecting their intention. Background COVID-19 patients undergoing mechanical ventilation have many care needs and pose more challenges for nurses, which might adversely affect nurses' intention toward caring behavior. Methods A cross-sectional study was conducted by using simple random sampling to recruit 598 nurses from five tertiary hospitals in Sichuan Province, China. The participants responded to an online questionnaire that included questions on demographic characteristics; the Attitude, Subjective Norms, and Behavioral Intention of Nurses toward Mechanically Ventilated Patients (ASIMP) questionnaire; the Nursing Professional Identity Scale (NPIS); and the Compassion Fatigue-Short Scale (CF-Short Scale). ANOVA, Spearman correlation analysis, and multiple linear regression were performed to analyze the data. Results The mean total behavioral intention score was 179.46 (± 14.83) out of a total score of 189.00, which represented a high level of intention toward caring for patients on mechanical ventilation. Multiple linear regression revealed that subjective norms (β = 0.390, P<0.001), perceived behavioral control (β = 0.149, P<0.001), professional identity (β = 0.101, P = 0.009), and compassion fatigue (β = 0.088 P = 0.024) were significant predictors of nurses' behavioral intention. Conclusions Most nurses have a positive behavioral intention to care for COVID-19 patients undergoing mechanical ventilation. The findings in this study provide some insight for developing effective and tailored strategies to promote nurses' behavioral intention toward caring for ventilated patients under the pandemic situation.